The first experimentally obtained dataset on processing parameters and properties of soft magnetic composites - Radovan Bures; Vasily A. Milyutin; Maria Faberova; Zuzana Bircakova; Peter Kollar; Jan Fuzer (Scientific Data)
Abstract The present work describes the process of the creation and analysis of the first dataset containing processing parameters and functional properties of soft magnetic composites (SMC). All data were obtained experimentally using Fe-3% MgO system. When creating samples, parameters such as a size of MgO nanoparticles, pressing pressure, sintering temperature, time and atmosphere were varied. In total, 282 samples with a unique combination of processing parameters were obtained. In each sample, density, real part of complex magnetic permeability at different frequencies, coercivity, and resonant frequency were measured. This allowed us to create the first experimentally obtained dataset devoted to SMC. Such dataset is necessary for implementing data-driven research in the field of SMCs, as well as for studying correlations in the chain: processing parameters – structure – properties. The dataset is currently being expanded both in terms of expanding the set of variable independent parameters and in terms of expanding the set of controlled properties. The dataset is hosted in Figshare open repository.